2003
DOI: 10.1161/01.cir.0000044386.27444.5a
|View full text |Cite
|
Sign up to set email alerts
|

Localization, Macromolecular Associations, and Function of the Small Heat Shock–Related Protein HSP20 in Rat Heart

Abstract: Background-The small heat shock proteins HSP20, HSP25, ␣B-crystallin, and myotonic dystrophy kinase binding protein (MKBP) may regulate dynamic changes in the cytoskeleton. For example, the phosphorylation of HSP20 has been associated with relaxation of vascular smooth muscle. This study examined the function of HSP20 in heart muscle. Methods and Results-Western blotting identified immunoreactive HSP20, ␣B-crystallin, and MKBP in rat heart homogenates. Subcellular fractionation demonstrated that HSP20, ␣B-crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
2
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 31 publications
4
69
2
1
Order By: Relevance
“…In the heart, Hsp20 is biochemically associated with ␣B-crystallin but localizes in distinct bands as does ␣B-crystallin and sarcomeric actin. This report appears to dissociate the effects of hypoxia on ␣B-crystallin and Hsp20 in the heart (Pipkin et al 2003). Hsp60 is a mitochondrial HSP associated with Hsp10.…”
Section: Discussionmentioning
confidence: 67%
“…In the heart, Hsp20 is biochemically associated with ␣B-crystallin but localizes in distinct bands as does ␣B-crystallin and sarcomeric actin. This report appears to dissociate the effects of hypoxia on ␣B-crystallin and Hsp20 in the heart (Pipkin et al 2003). Hsp60 is a mitochondrial HSP associated with Hsp10.…”
Section: Discussionmentioning
confidence: 67%
“…First, we have previously shown that Hsp20 confers protection via inhibition of the Bax/ caspase-3 pro-apoptotic pathway (16), which may be subject to regulation by its phosphorylation state. Second, pSer 16 Hsp20 may help maintain cardiomyocyte integrity via stabilization of the cytoskeleton (16,27). Finally, Hsp20 may form both homologous and heterologous macromolecular structures (3,27,28), which may be affected by its phosphorylation status.…”
Section: Discussionmentioning
confidence: 99%
“…Second, pSer 16 Hsp20 may help maintain cardiomyocyte integrity via stabilization of the cytoskeleton (16,27). Finally, Hsp20 may form both homologous and heterologous macromolecular structures (3,27,28), which may be affected by its phosphorylation status. Overall, loss of the Hsp20 ability to become phosphorylated may have detrimental effects on its cellular functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromatography with molecular sieving columns revealed that HSP20 and ␣B-crystallin were associated in an aggregate of Ϸ200 kDa, and the phosphorylation of HSP20 was determined by 2D gel electrophoresis and immunoblotting. 33 Signal transduction protein complexes and their activation, eg, protein kinase C activation, were analyzed as described above by subcellular fractionation, detergent extraction, and Western blotting in cultures of neonatal rat ventricular myocytes after electric stimulation. 34 Caveolae are plasma membrane invaginations that are enriched in cholesterol, sphingolipids, and the marker protein caveolin.…”
Section: Subcellular Fractionation and Protein Identification In Cardmentioning
confidence: 99%